The influence of information literacy towards students' academic performance / Wan Nor Haliza Wan Mokhtar ... [et al.] - Wan Mokhtar, Wan Nor Haliza; Rambli, Yanty Rahayu; Jemat, Jemauri Ajerama; Hussin, Norhayati (Faculty of Information Management, 2023)
This study investigated the influence of information literacy on the academic performance of Master's students in the Faculty of Information Management. UiTM Puncak Perdana Campus, Selangor, Malaysia. The study applied a quantitative approach and adopted a survey method. The data collected were analysed by using SPSS software Version 26. The study revealed that most respondents are well versed in searching Skills, retrieval skills, and evaluating Skills. Therefore, this paper recommends educational courses in the form of workshops to be presented to students on the topics related to searching, critical thinking, using the suitable methodologies for studying (including writing essays), as well as research attitude (including conducting research). Besides that, this study suggests that future studies should be conducted in the context of students' academic performance by using other skills such as study and research skills with different populations and institutions.